(untitled) (Scottish Historical and Archaeological Internet Reports, 2011)
Since 1987 Sheffield University and latterly other universities have carried out archaeological investigations of archaeological sites on the machair of South Uist, Barra and the southern isles of the Western Isles (Outer Hebrides) as part of the SEARCH project [Sheffield Environment and Research Campaign in the Hebrides]. The remains often survive extremely well as stone-walled dwellings with intact floors, set within deeply stratified settlement mounds, dating from the Beaker period to the Post-Medieval period. This exceptional archaeological resource has come under threat especially from rabbit-burrowing as well as from coastal and wind erosion. The good preservation of floors and other features has helped in the development of new archaeological methodologies and techniques as well as providing new evidence of Hebridean life through the millennia. A bibliography of the SEARCH project is appended.